Muscle morphology and jump performance: gender and intermuscular variability - Alegre, L. M.; Lara, A. J.; Elvira, J. L. L.; Aguado, X. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: The present study aimed 1) to investigate the gender differences in jump performance and muscle architecture between men and women; and 2) to determine whether the differences in jump performance could be attributed to gender differences in the METHODS:Sixty-two subjects volunteered for the study (34 women and 28 men): 19 club-level volleyball players, 20 physical education students, and 23 sedentary individuals. They performed trials of countermovement jumps (CMJ) and the muscle architecture of the vastus lateralis (VL), gastrocnemius medialis (GM), and lateralis (GL) were analyzed at rest by ultrasonography. RESULTS: There were significant differences in jump performance between men and women (CMJ height: 0.388±0.056 m in men and 0.279±0.060 m in women, P<0.001). There were also significant gender differences in the VL muscle thickness, while the relative fascicle length was significantly different in the three muscles studied, with longer fascicles in the VL muscle in men and longer fascicles in the gastrocnemii in women. There were significant associations between the VL muscle size and jump performance (r=0.49-0.50, P<0.001), and non linear relationships between muscle size parameters and pennation angles (R2=0.67-0.77, P<0.001). CONCLUSIONS: These results confirm that there are gender differences in the muscle architecture of people with a wide physical activity background. The gender differences found in the VL muscle size partially explained the differences in jump performance.